2022
DOI: 10.1080/21680566.2022.2152129
|View full text |Cite
|
Sign up to set email alerts
|

How gaps are created during anticipation of lane changes

Abstract: The pre-insertion process called anticipation is an essential component of a lane-changing manoeuvre. There is little empirical research regarding the impact of anticipation. Thus, this paper aims to explore the behaviour of the new follower (NF) in the target lane when it encounters anticipation by using new trajectory datasets. The changing magnitude of the reaction pattern is proposed to identify the NF's behaviour. We find that the anticipation significantly affects the NF's movement in terms of gap creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In actual traffic, drivers typically exhibit cooperative behavior (e.g. Kondyli and Elefteriadou, 2012), including the phenomenon of 'anticipation' by the new follower (Chen et al, 2023) and 'relaxation' after the lane change has occurred Zheng et al (2013). The latter entails that drivers sometimes tolerate small gaps, knowing that these gaps will soon expand again (Daamen et al, 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In actual traffic, drivers typically exhibit cooperative behavior (e.g. Kondyli and Elefteriadou, 2012), including the phenomenon of 'anticipation' by the new follower (Chen et al, 2023) and 'relaxation' after the lane change has occurred Zheng et al (2013). The latter entails that drivers sometimes tolerate small gaps, knowing that these gaps will soon expand again (Daamen et al, 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Then [10] investigated the effect of microscopic characteristics and analyzed the decision-making model by changing the lanes of heavy vehicles. [8], [11], [12], [13] conducted several studies on lane changes aiming to investigate the decision-making process of lane change manoeuvres for various drivers based on a two-stage test-drive, investigate the impact of a lane change strategy on expressway traffic operations, and analyze the behavior of new follower vehicles changing lanes in the target lane when facing anticipation (pre-insertion process). The research conducted has its own variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[5] focused on the motivation to change lanes, the selection of the target lane, and the decision to change lanes. Whereas [8], [11], [12], [13] focuses on strategies for changing lanes, time, distance, speed, density, and gap width.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using real-world vehicle-level trajectory data, Yang et al (2019b) examined 5339 LC trajectory samples and found that approximately 44% of new followers would decelerate when they noticed the LC motivation in the adjacent lane. Chen et al (2022) investigated the impact of anticipation on the new follower and found evidence of its significance. To this end, they developed two binary logit models, demonstrating that including the anticipation-related factors significantly improved the prediction accuracy regarding whether the new follower changes its driving behavior during anticipation.…”
Section: Impact Of Lane-changing Anticipationmentioning
confidence: 99%
“…Although some recent empirical studies have also reported similar negative impacts of anticipation on the new follower's behavior (Yang et al, 2019a;Chen et al 2022), relatively limited attention has been paid to quantifying these impacts. As a result, there is currently a lack of clarity regarding a CF model that can accurately describe the new follower's behavior during anticipation.…”
Section: Introductionmentioning
confidence: 99%